Ice burn in puerperal breast: case report - Costa, Márden Pinheiro Teixeira; Cavalcante, Francisco Pimentel (Mastology, 2018)
Burns are among the most severe injuries the human body can withstand, as they are life-threatening and therefore require prompt treatment with debridement and use of biological substitutes for a better prognosis. This case report concerns an 18-year-old patient on the 42nd day of puerperium who used ice packs on the right breast to alleviate breast engorgement and pain. After a prolonged period of use, it progressed to hyperemia and, subsequently, an extensive area of necrosis in the skin of the right breast, reaching the subcutaneous adipose tissue, compatible with a third-degree burn. Surgical debridement of the necrotic areas was performed, followed by the use of biological skin substitutes until complete healing of the local skin, not requiring grafting at first. Cryotherapy should be used with caution. Treatment with clinical support and fast surgical intervention can minimize the impact of burns.